HUBUNGAN ANTARA KECENDERUNGAN MAHASISWA MENGGUNAKAN JENIS APLIKASI GADGET DENGAN KEPEKAAN SOSIAL - Rahmah, Maudina; Sukarelawati, Sukarelawati; Fitriah, Maria (Universitas Djuanda Bogor, 2018)
The purpose of this research was (1) to knowed the types of application on gadget which tend to be used by the students, (2) to know the level of usage of application type which tends to be used by the students, (3) to knowed the social sensitivity level of student of gadget user, and (4) to knowed the relationship of using gadgets with students' social sensitivities. This research used descriptive type method with quantitative approach which was done by survey research and tested using Rank Spearman correlation. The result of the research showed that (1) WhatsApp application in gadget tends to be used by the students shown on the activity of sending messages with very good category, (2) the level of application of the type of application used by the majority students on the activity of WhatsApp application as communication media to establish silaturrahmi or cultivate brotherhood with good category,Â (3) the level of social sensitivity of students were in good category indicated in the indicators can not live alone, (4) there was a significant relationship between the tendency of students using the type of gadget application with social sensitivity with the level of correlation coefficient in the medium category.